Emissions of nitrated and oxygenated polycyclic aromatic hydrocarbons bound to coarse particles from solid fuel combustion - Feng, Yaoxing; Wang, Jinze; Sun, Jie; Cui, Zhanpeng; Chen, Qi; Mao, Kang; Lei, Yali; Zhang, Peng; Du, Wei; Shi, Jianwu; Pan, Bo (Chemosphere (Oxford), 2024)
Parent polycyclic aromatic hydrocarbons (PAHs) emitted by residential sector have been well studied, however, data on PAHs derivatives such as nitrated PAHs (nPAHs) and oxygenated PAHs (oPAHs) are scarce. In this study, emission factors (EFs) of PM10-bound nPAHs and oPAHs from the combustion of eight different solid fuels in three different stoves in rural homes were measured in field, and a total of twelve fuel-stove combinations were included. Results showed that the field-based EFs for different fuel-stove combinations varied over three orders of magnitude, which ranged from 3.3 to 514 μg/kg and from 0.1 to 214 mg/kg for nPAHs and oPAHs, respectively. Biomass burning had 2.2 and 14.8 times higher EFs values of nPAHs and oPAHs compared with coal burning. The size distribution pattern of PAHs derivatives confirmed that they prefer to bind to fine particles. The composition profiles of nPAHs and oPAHs varied largely in different coals, while slightly in different biomasses. Furthermore, the nPAHs and oPAHs composition profiles varied largely from emission source to the nearby atmosphere, implying that the composition of PAHs derivative changed during small-scale transport process. Results from this study can fill in the data gap in PAHs derivative emissions from residential solid fuel combustion and help to evaluate the environmental and health impacts of residential solid fuel combustion. [Display omitted] •Field-based EFs of PAHs derivatives from different fuel-stove combinations varied hugely.•PAHs derivatives preferred to bind to fine particles than coarse particles.•The composition profiles of PAHs derivatives varied largely among different coals.•From emission source to the nearby atmosphere, the composition of PAHs derivatives changed greatly.